The Utilization of Modified Chitosan from Shrimp Shell As Photodegradation of Pesticides Paraquat Dichloride - Risfidian Mohadi; Neza Rahayu Palapa; Rudi Hartono; Nurlisa Hidayati; Rozirwan (Science and Technology Indonesia, 2021)
In this study, the chitosan modification of shrimp shell has been made by impregnated the chitosan from shrimp shell with Ti/ZrO2 and ZrO2 to formed composite of chitosan-Ti/ZrO2 and chitosan-ZrO2. These composites were made by immobilization technique and characterized by FTIR and SEM-EDX. The chitosan-Ti/ZrO2 and chitosan-ZrO2 composite were used as a catalyst to degrade the pesticide paraquat dichloride in the presence of UV light (????= 257 nm). The photodegradation process of paraquat dichloride takes place under 10 watts UV light irradiation and was measured using spectrophotometer UV. The maximum degradation percentage of pesticide paraquat dichloride photodegradation by chitosan-Ti/ZrO2 and chitosan-ZrO2 composites are 61.97% and 57.97% within 30 minutes irradiation time.